Significant parameters for the surface roughness in incremental forming process - Echrif, Salah B. M.; Hrairi, Meftah (Taylor & Francis, 2014)
The features of the incremental sheet forming (ISF) process allow it to meet a wide array of customer preferences. In this paper, the variation of surface roughness (SR) in a negative ISF process was systematically studied. The variation was investigated by means of four different process parameters, namely, the vertical step size, forming tool diameter, spindle speed, and feed rate. By using Taguchi analysis with the help of design of experiment and analysis of variance (ANOVA), the effects of the above four process parameters have been studied to optimize parameter levels to realize minimum SR. The results illuminated which parameters have the greatest effect on SR variation, namely, tool size and vertical step size. The confirmation test also showed that the response tables and graphs from Taguchi analysis and ANOVA constitute effective and efficient methods for determining each design parameter’s optimal level to produce the minimum value of the SR.